Role of six cytokines and bone metabolism biomarkers in gingival crevicular fluid in patients undergoing fixed orthodontic appliance treatment in comparison with aligners: a clinical study - Kamran, Muhammad Abdullah; Alnazeh, Abdullah A.; Almagbol, Mohammad; Almoammar, Salem; Alhaizaey, Ali Hasan A.; Alshahrani, Ibrahim (The Angle orthodontist, 2023)
The objective of this study was to assess bone biomarkers and cytokines in patients with conventional labial appliances (CLAs) and aligners. Participants were recruited to undergo orthodontic treatment with CLAs and aligners according to predefined inclusion and exclusion criteria. Periodontal examination was accomplished at baseline and 4 weeks using the plaque index (PI), gingival index (GI), and bleeding on probing (BoP). Samples of gingival crevicular fluid (GCF) were collected at baseline (T0) before the start of treatment and at the 1-month follow-up (T1) to assess bone metabolic and inflammatory biomarkers. GCF from participants with CLAs and aligners was evaluated with enzyme-linked immunosorbent assay. Comparison between labial conventional orthodontic treatment and aligners were assessed using an unpaired t-test. The difference between T0 and T1 was measured using a paired t-test. BoP, PI, and GI demonstrated no significant difference between participants treated with aligners and subjects with CLAs at baseline and at 4 weeks (P > .05). Bone markers and other biomarkers (tumor necrosis factor α, interleukin [IL]-α, IL-2, IL-6, and IL-8) showed significant differences (P < .05). Also, a significant difference between CLAs and aligners was noted among all biomarkers (P < .05) except IL-β. Aligners and CLAs increase the level of inflammatory and bone metabolic biomarkers after 1 month.